Systematic evaluation of the QualityRights programme in public mental health facilities in Gujarat, India. (April 2021) - Pathare, Soumitra; Funk, Michelle; Drew Bold, Natalie; Chauhan, Ajay; Kalha, Jasmine; Krishnamoorthy, Sadhvi; Sapag, Jaime C.; Bobbili, Sireesha J.; Kawade, Rama; Shah, Sandeep; Mehta, Ritambhara; Patel, Animesh; et al.
Abstract : Background: Recognising the significant extent of poor-quality care and human rights issues in mental health, the World Health Organization launched the QualityRights initiative in 2013 as a practical tool for implementing human rights standards including the United Nations Convention on Rights of Persons with Disabilities (CRPD) at the ground level. Aims: To describe the first large-scale implementation and evaluation of QualityRights as a scalable human rights-based approach in public mental health services in Gujarat, India. Method: This is a pragmatic trial involving implementation of QualityRights at six public mental health services chosen by the Government of Gujarat. For comparison, we identified three other public mental health services in Gujarat that did not receive the QualityRights intervention. Results: Over a 12-month period, the quality of services provided by those services receiving the QualityRights intervention improved significantly. Staff in these services showed substantially improved attitudes towards service users (effect sizes 0.50–0.17), and service users reported feeling significantly more empowered (effect size 0.07) and satisfied with the services offered (effect size 0.09). Caregivers at the intervention services also reported a moderately reduced burden of care (effect size 0.15). Conclusions: To date, some countries are hesitant to reforming mental health services in line with the CRPD, which is partially attributable to a lack of knowledge and understanding about how this can be achieved. This evaluation shows that QualityRights can be effectively implemented even in resource-constrained settings and has a significant impact on the quality of mental health services.